2023
DOI: 10.3390/agriculture13112146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silicon Alone and Combined with Organic Matter and Trichoderma harzianum on Sorghum Yield, Ions Accumulation and Soil Properties under Saline Irrigation

José Orlando Nunes da Silva,
Luiz Guilherme Medeiros Pessoa,
Emanuelle Maria da Silva
et al.

Abstract: The action of silicon as a salt stress mitigator has been investigated in isolation, and its combined efficacy with other salt stress mitigators needs to be addressed. This work verified whether silicon, in combination with organic matter and Trichoderma harzianum, enhances the production of forage sorghum under saline irrigation and its effects on soil properties. The field experiment was conducted in Parnamirim (PE), a semiarid region of Brazil. Forage sorghum (Sorghum sudanense (Piper) Stapf) was irrigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 108 publications
1
0
0
Order By: Relevance
“…In addition, even with a higher soil salt concentration, the salinity attenuators effectively controlled the salt effect stress, decreasing the plants absorption of Na + and Cl − . In other research, Silva et al [35], by testing the same attenuators and combinations as this study in sorghum (Si + OM, Si + T, and Si + OM + T), showed that the Si combinations reduced toxic ion absorption (Na + and Cl − ) and favored nutrient ion absorption (K + ), resulting in significant gains in biomass.…”
Section: Quinoa Growth and Nutritional Statussupporting
confidence: 60%
“…In addition, even with a higher soil salt concentration, the salinity attenuators effectively controlled the salt effect stress, decreasing the plants absorption of Na + and Cl − . In other research, Silva et al [35], by testing the same attenuators and combinations as this study in sorghum (Si + OM, Si + T, and Si + OM + T), showed that the Si combinations reduced toxic ion absorption (Na + and Cl − ) and favored nutrient ion absorption (K + ), resulting in significant gains in biomass.…”
Section: Quinoa Growth and Nutritional Statussupporting
confidence: 60%